2005
DOI: 10.1021/ol051030f
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base-Catalyzed Additions of Alkynes Using Trialkoxysilylalkynes

Abstract: [reaction: see text]. The Lewis base-catalyzed additions of alkynyl nucleophiles to aldehydes, ketones, and imines is described. Mechanistic studies strongly indicate that the use of new triethoxysilylalkynes facilitates access of a reactive hypervalent silicate intermediate. This activated carbon nucleophile subsequently undergoes rapid addition to carbonyl compounds and imines, thus affording the secondary and tertiary propargyl systems in moderate to high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…16 The enantioselective alkynylations of aldehydes have been widely investigated, however, few successful reports of the alkynylation of ketones exist due to their low reactivities. 17,18 As the reactivity of trialkoxysilylalkynes are sufficiently high to react with ketones, 8 we next started to investigate the alkynylation of ketones.…”
Section: Alkynylation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The enantioselective alkynylations of aldehydes have been widely investigated, however, few successful reports of the alkynylation of ketones exist due to their low reactivities. 17,18 As the reactivity of trialkoxysilylalkynes are sufficiently high to react with ketones, 8 we next started to investigate the alkynylation of ketones.…”
Section: Alkynylation Of Ketonesmentioning
confidence: 99%
“…4e7 Recently another access to the propargylic alcohols was reported by Scheidt, who found that alkoxides activated trialkoxysilylalkynes to react with ketones as well as aldehydes. 8,9 In their report, they postulate the formation of hypervalent silicate 10 from trialkoxysilylalkyne and alkoxide. We previously reported that lithium binaphtholate activated trimethoxysilyl enol ethers to form hypervalent silicate, which reacted with an aldehyde to afford an aldol adduct in high chemical and optical yields.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a study on the Lewis base-catalyzed addition of alkynyl nucleophiles, Scheidt has described the alkynylation of (S)-tert-butylsulfinyl imines 18 with 1-triethoxysilyl-1-hexyne in the presence of KOEt and 18-crown-6 [29] The reaction is supposed to proceed via a reactive hypervalent silicate intermediate 37, to give compounds 20 with excellent yield (95%) and high selectivity (20:1) favoring the (R,S s ) diastereomer (Scheme 14, entry 4). Alternative alkynyl organometallic nucleophiles were either less selective (M = K) or gave an opposite diastereoselectivity (M = Li or M= MgEt).…”
Section: Addition Of Other Organometallic Reagentsmentioning
confidence: 99%
“…Herein, we report for the first time the efficient asymmetric synthesis of (E)-2-arylidene-1,4-diphenylbut-3-yn-1-amines in high diastereoselectivity via the addition of alkynylzinc species to N-tert-butansulfinyl-A C H T U N G T R E N N U N G imines, which are stable, easy to prepared, and widely used for various applications. [5][6][7][8][9] In our work, we used Ellmans enantiomerically pure, R-configured N-tert-butanesulfinylimines, which can be used as chiral nitrogen-containing intermediates for the preparation of a wide range of chiral amines. The asymmetric addition of an alkynylzinc to (R)-tert-butylsulfinylbenzaldimine (1a) led to the formation of two major compounds, 2a and 3a.…”
mentioning
confidence: 99%